THE STUDY OF THE MINERAL CHEMICAL COMPOSITION OF THE YAKUT SAPONITE MINERAL AND THE PHYSICO-CHEMICAL BASES OF COMPLEX TRACE ELEMENTS (American Journal of Pedagogical and Educational Research, 2022)
The conducted chemical studies show that in the selected saponites of the upper layer the content of chemical elements is CAO - 22.57%; MdO - 20.99; SiO2 - 26.30; K2O - 1.23% and Fe2O3 - 7.92% and in the lower layer the content of chemical elements is CaO2 1.48%; MgO - 19.75; SiO2 - 27.41; K2O - 1.31% and Fe2O3 - 8.23%. . The mass loss when the saponite sample is heated to 1000 °C is 9.87%. The endoeffects in the range of 90-160 °C correspond to the removal of adsorbed water on the inner surface of the intercrystal minerals that make up saponite. Endoeffects in the range 160-330°C correspond to the beginning of the removal of constitutional water minerals A further increase in temperature is also accompanied by dehydration of mineral impurities.